What drives students' cyber entrepreneurial intention: The moderating role of disciplinary difference. (December 2016) - Wang, Yi-Shun; Lin, Shin-jeng; Yeh, Ching-Hsuan; Li, Ci-Rong; Li, Hsien-Ta
Highlights: This study explores the determinants of university students' cyber entrepreneurial intention. Both intrinsic and extrinsic cyber entrepreneurial motivations positively influence cyber entrepreneurial intention. Conscientiousness, openness to experience, and agreeableness positively affect intrinsic cyber entrepreneurial motivation. Extraversion, conscientiousness, and neuroticism positively affect extrinsic cyber entrepreneurial motivation. IT-related education enhances the positive effect of extrinsic cyber entrepreneurial motivation on cyber entrepreneurial intention. Abstract: With the growth of the e-commerce industry, developing a better understanding of what drives students' cyber entrepreneurial intention has become an important issue for academics and practitioners. This study explores the determinants of students' cyber entrepreneurship intention by investigating the relationships between the Big Five personality traits, intrinsic/extrinsic cyber entrepreneurial motivation, and cyber entrepreneurial intention. Structural equation modeling is employed to analyze data gathered from 450 final-year undergraduates. The results indicate that both intrinsic and extrinsic cyber entrepreneurial motivations positively influence cyber entrepreneurial intention. Besides, conscientiousness, openness to experience, and agreeableness positively affect intrinsic cyber entrepreneurial motivation while extraversion, conscientiousness, and neuroticism positively affect extrinsic cyber entrepreneurial motivation. Disciplinary difference (IT-related vs. non-IT-related) moderates the effect of extrinsic cyber entrepreneurial motivation on cyber entrepreneurial intention. By incorporating both personality traits and motivations into the analysis of cyber entrepreneurial intention, this study provides several important theoretical and practical implications for promoting cyber entrepreneurship.